2023
DOI: 10.3390/antibiotics12060980
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association between the Existence of CRISPR/Cas Systems with Antibiotic Resistance, Extended Spectrum β-Lactamase and Carbapenemase Production in Multidrug, Extensive Drug and Pandrug-Resistant Klebsiella pneumoniae

Noor A. Jwair,
Mushtak T. S. Al-Ouqaili,
Farah Al-Marzooq

Abstract: Antimicrobial resistance, with the production of extended-spectrum β-lactamases (ESBL) and carbapenemases, is common in the opportunistic pathogen, Klebsiella pneumoniae. This organism has a genome that can contain clustered regularly interspaced short palindromic repeats (CRISPRs), which operate as a defense mechanism against external invaders such as plasmids and viruses. This study aims to determine the association of the CRISPR/Cas systems with antibiotic resistance in K. pneumoniae isolates from Iraqi pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
1
15
1
Order By: Relevance
“…In recent years, K. pneumoniae has emerged as a significant nosocomial and opportunistic pathogen. Antibiotic resistance, with the production of extended-spectrum β-lactamases (ESBL), carbapenemases or aminoglycosides resistance, is common in K. pneumoniae ( Raouf et al., 2022 ; Jwair et al., 2023 ; Khoshnood et al., 2023 ), which brings big challenges to the therapy of infection of K. pneumoniae . The emergence of carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP) has exhibited prevalence since 2010 ( Lan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, K. pneumoniae has emerged as a significant nosocomial and opportunistic pathogen. Antibiotic resistance, with the production of extended-spectrum β-lactamases (ESBL), carbapenemases or aminoglycosides resistance, is common in K. pneumoniae ( Raouf et al., 2022 ; Jwair et al., 2023 ; Khoshnood et al., 2023 ), which brings big challenges to the therapy of infection of K. pneumoniae . The emergence of carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP) has exhibited prevalence since 2010 ( Lan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequences of gyrA, gyrB , and parC were determined by the dideoxy chain termination method. 11 Furthermore, to compare the mRNA expression of the drug efflux pump gene acrA 12 , 13 between the parental strain and the strain exposed for 25 days, total RNA was extracted using TRI Reagent LS (Molecular Research Center, Inc., Cincinnati, OH). The mRNA expressions were quantified by the iTaq Universal CYBR Green One-step kit (BIO-RAD) and CFX Connect Real-Time System (BIO-RAD).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been reported that there exists an inverse association between the existence of CRISPR/Cas system with antibiotic resistance, ESBL and carbapenemase production in antibiotic resistant bacteria, such as K. pneumonia . 73 In addition, the prevalence of CRISPR/Cas system and its possible association with antibiotic resistance has been reported in E. faecalis and E. faecium . 74 …”
Section: Crispr/cas System and Its Typesmentioning
confidence: 99%